A Morphological Analysis of Affixes in All The Bright Places Movie - Supri, Ida Zuraida; Sitompul, Agnessya Yenanda; Rizky, Dimas; Falaq, Fasya Nurulita; Herlansyah, Muhammad Arghi; Andini, Rifkia (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to identify the types of affixes and to analyze the changes of the word classes found in All the Bright Places movie. The method used in this research is descriptive qualitative by employing the following steps: downloading, reading, identifying, categorizing, analyzing, and drawing a conclusion. The theory of types of affixes used is as proposed by [1] and the theory of a class of words is by [2]. The results indicate that two types of affixes found in the movie are derivational and inflectional affixes. Out of 122 data, 82 are inflections (pluralism and tenses) and 40 data are derivations. The changes of the class of words that occur are adverb to the adjective, adjective to a noun, adjective to the verb, noun to verb, adverb to the verb, noun to adjective, the verb to noun, and verb to the adjective.